Il "Foro Provinciale" di Tarraco (Hispania Citerior): tecniche e processi edilizi - VINCI, MARIA SERENA (DAN@, 2020)
The grand building complex in Tarraco known as the "Provincial Forum" is one of the most emblematic imperial-era monuments in the western Roman provinces. Based on the observation and detailed analysis of the archaeological evidence from an original perspective, this monograph proposes an investigation of the technical aspects and Roman building processes involved in the three main areas of the monument: the Worship Area, the Representation Square and the Circus. The construction of one of the key monuments in the Roman West was extensively influenced by local stone resources, in particular limestone, coming from the quarries near the colony. The use of this stone material have generated the search for architectural solutions, combination of material and technique, that have become the identifying characteristic not only of the monument, but also of the town's image. The analysis of the construction process was key to understanding the ancient structures. It revealed the dynamic nature of their construction, the result of a plan that was constantly changing and adapting to external conditions or to the requirements of the construction site. It shows a process that reflects the existence of a plan in continuous evolution, a manifestation of the essence of the building site (cantiere di costruzione) and its architecture.